2021
DOI: 10.3390/jof7020132
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Commercial PCR Assays for the Detection of Azole-Resistant Aspergillus fumigatus from Respiratory Samples of Immunocompromised Patients

Abstract: This is the first study comparing three commercially available PCR assays for the detection of Aspergillus DNA from respiratory specimen of immunocompromised patients and the presence of cyp51A gene mutations. Bronchoalveolar lavages (BALs, N = 103) from patients with haematological/oncological underlying diseases were retrospectively investigated. The performance of three PCR assays, namely MycoGENIE®Aspergillus fumigatus Real-Time PCR Kit (Adamtech), Fungiplex®Aspergillus Azole-R IVD Real-Time PCR Kit (Bruke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This has the advantage of limiting cross-amplification, but has a direct impact on the LOD. While with monogenic markers LOD is in the nanograms range, lower LOD can be achieved with lower polygenic markers, ranging from 1000 to 100 femtograms [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. The SYBR-Green assay was chosen to provide rapid and accurate results in a cost-effective manner, providing a tool to help in the diagnosis of filamentous fungi infections, especially for low-income health facilities in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…This has the advantage of limiting cross-amplification, but has a direct impact on the LOD. While with monogenic markers LOD is in the nanograms range, lower LOD can be achieved with lower polygenic markers, ranging from 1000 to 100 femtograms [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. The SYBR-Green assay was chosen to provide rapid and accurate results in a cost-effective manner, providing a tool to help in the diagnosis of filamentous fungi infections, especially for low-income health facilities in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Antifungal therapy or prophylaxis did not influence PCR results and therefore should not be the reason for the low positivity rate. 19 Within the study period, neither other Aspergillus species than A. fumigatus nor Mucorales were detected by culture or PCR from patients with CAPA. Delineating differences regarding separate COVID‐19 waves was not possible because most of the cases were derived from the second wave.…”
Section: Discussionmentioning
confidence: 93%
“…Antifungal therapy or prophylaxis did not influence PCR results and therefore should not be the reason for the low positivity rate. 19 Mutation analysis showed that one isolate (number 14) exhibited a TR34/L98H alteration and one (number 3) multiple mutations (F46Y, M172V and E427K). TR34/L98H is an environmentally occurring resistance mutation and is widespread across multiple continents.…”
Section: Discussionmentioning
confidence: 99%
“…including: Aspergillus niger Aspergillus nidulans Aspergilus terreus Aspergillus flavus Aspergillus versicolor Aspergillus glaucus - BAL BA NA 90 – 100%/97 – 97.8% [ 196 , 197 ] MycoReal Aspergillus (Ingenetix) Real-time PCR (melt curve Analysis) ITS2 region Aspergillus fumigatus Aspergillus flavus Aspergillus nidulans Aspergillus niger Aspergillus terreus - BAL Blood CSF Tissues NA NA [ 189 , 198 , 199 ] MycoGENIE® Aspergillus Species and MycoGENIE® Aspergillus fumigatus and resistance TR34/L98H (Ademtech) Quadruplex real-time PCR 28S rRNA Aspergillus spp. including: Aspergillus fumigatus TR34/L98H mutations Serum BAL Biopsy NA 71 – 100%/84.6 – 100% [ 195 , 200 , 201 ] Asp ID (OlmDiagnostics) Multiplex real-time PCR Unknown Aspergillus spp. including: Aspergillus terreus - BAL 90 minutes (excluding DNA extraction) 94.1%/76.5% [ [200] , [201] , [202] ] Cand ID® and Auris ID® (OlmDiagnostics) Multiplex real-time PCR Unknown Cand ID: Candida albicans Candida dubliniensis Candida glabrata ...…”
Section: Nucleic Acid Molecular Methodologiesmentioning
confidence: 99%